Acute Hepatitis C in Patients with HIV - Boesecke, Christoph; Rockstroh, Jürgen Kurt (Seminars in Liver Disease, 2012)
Almost 10 years ago clinicians started to note the first cases of an outbreak of acute hepatitis C (AHC) infections among human immunodeficiency virus- (HIV-) positive men who have sex with men (MSM) in Europe, soon followed by similar reports from the United States and Australia. In the absence of randomized controlled treatment trials in AHC, coinfection expert consensus recommendations based upon published data from uncontrolled clinical and cohort studies give guidance on best clinical management. Pegylated interferon in combination with weight-adapted ribavirin is still recommended as the treatment of choice for all HCV genotypes. For patients developing a rapid virologic response, treatment duration of 24 weeks is recommended. If antiviral therapy was initiated within 24 weeks after diagnosis, high sustained virologic response rates of 60 to 80% have been observed. Prevention and screening efforts along with early anti-HCV therapy have to be intensified to allow for control of viral dissemination as the current epidemic of AHC particularly among MSM is still ongoing.
Keywords: acute hepatitis C virus; human immunodeficiency virus; HIV; treatment; interferon; ribavirin